2011
DOI: 10.1007/s11306-011-0301-8
|View full text |Cite
|
Sign up to set email alerts
|

Transgressive segregation of primary and secondary metabolites in F2 hybrids between Jacobaea aquatica and J. vulgaris

Abstract: Hybridization between plant species can have a number of biological consequences; interspecific hybridization has been tied to speciation events, biological invasions, and diversification at the level of genes, metabolites, and phenotypes. This study aims to provide evidence of transgressive segregation in the expression of primary and secondary metabolites in hybrids between Jacobaeavulgaris and J. aquaticus using an NMR-based metabolomic profiling approach. A number of F2 hybrid genotypes exhibited metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
3
15
0
1
Order By: Relevance
“…As a consequence, novel combinations, extreme concentrations of secondary metabolites, or in some cases, metabolites not found in both parents are expressed as a result of sexual reproduction. Indeed, several studies focusing on the impact of hybridization among related plant species on metabolomic profiles in their progeny support this hypothesis (Kirk et al 2004(Kirk et al , 2005(Kirk et al , 2012.…”
Section: Genomic Variation As Raw Materials For Metabolic Innovationmentioning
confidence: 94%
“…As a consequence, novel combinations, extreme concentrations of secondary metabolites, or in some cases, metabolites not found in both parents are expressed as a result of sexual reproduction. Indeed, several studies focusing on the impact of hybridization among related plant species on metabolomic profiles in their progeny support this hypothesis (Kirk et al 2004(Kirk et al , 2005(Kirk et al , 2012.…”
Section: Genomic Variation As Raw Materials For Metabolic Innovationmentioning
confidence: 94%
“…Hardig et al 2000). Also, it has been found that these additional markers may unveil hybrid individuals that go undetected when using problematic DNA markers such as RAPD or AFLP (e.g., Kirk et al 2012). However, the main reason to study phenotypic and chromosomal traits in hybrids is that they may give insights of their ecological performance.…”
Section: Genetic Data Employed For Hybrid Recognition: Chromosome Nummentioning
confidence: 99%
“…Metabolomics tools have been used to evaluate the impact of the genotype and the environment on the quality of plant growth in the study of interpecific hybrids between Jacobaea aquatica and J. vulgaris (common weeds native to Northern Eurasia). An NMR-based metabolomics profiling approach was used to correlate the expression of high and low concentrations of particular compounds, including phenylpropanoids and sugars, with results of quantification of genetically controlled differences between major primary and secondary metabolites [81]. In melon (Cucumis melo L.), metabolomic and elemental profiling of fruit quality were found to be affected by genotype and environment [82].…”
Section: Plant Metabolomics and Applicationsmentioning
confidence: 99%